Impact of COVID-19 Pandemic on University Students' Physical Activity Levels: An Early Systematic Review - López-Valenciano, Alejandro; Suárez-Iglesias, David; Sanchez-Lastra, Miguel A.; Ayán, Carlos (Frontiers in Psychology, 2021)
Purpose: This systematic review aimed to analyze the impact that the COVID-19 lockdown had on the amount of physical activity performed by university students. Materials and Methods: A systematic electronic search for studies providing information regarding physical activity levels pre and during COVID-19 pandemic in university students was performed up to 20th October 2020. The risk of bias of external validity quality of included studies was assessed by means of those the Newcastle-Ottawa Scale (NOS). The quality of the evidence for main outcomes was graded using the Grading of Recommendations Assessment, Development and Evaluation (GRADE) approach. Results and Conclusions: A total of 10 studies were selected. Physical activity levels were assessed by means of questionnaires (10 studies) and accelerometer (1 study). Risk of bias was regarded as low and high in six and four investigations respectively. The quality of evidence was downgraded to low. A significant reduction of physical activity levels were observed in 9 studies. Compared to pre-lockdown values, five studies showed a reduction of light/mild physical activity (walking) between 32.5% and 365.5%, while seven studies revealed a reduction of high/vigorous physical activity between 2.9% and 52.8%. Walking, moderate, vigorous and total physical activity levels have been reduced during the COVID-19 pandemic confinements in university students of different countries. Despite of the reductions, those who met the current minimum PA recommendations before the lockdown generally met the recommendations also during the confinements.